On the relevance of professional activities in the modern securities market - A. P. Syrbu; A. V. Sinelnikov; V. I. Menshchikova (Путеводитель предпринимателя, 2020)
The article examines the types of professional activities in the modern securities market, assesses their relevance. A description is given of the types of activities in the securities market that are not professional, but are very similar in their tasks and functions to professional activities; proposals are made to change the composition of modern activities in the securities market in order to increase the efficiency of its functioning. It is concluded that there is a need to divide professional activities in the financial market into two types: professional intermediaries and professional participants providing settlement and accounting services in the financial market.